WORKING CAPITAL MANAGEMENT AND MANUFACTURING PERFORMANCE IN NIGERIA - Adedeji Daniel Gbadebo (Gusau Journal of Accounting and Finance, 2025)
Effective working capital is necessary for financial growth, sustainability, reliable liquidity and profitability of a firm. Management working capital involve the optimization of inventory, debtors and creditor to ensure profitability and liquidity of a firm. The paper aims to show how working capital management affect the performance of manufacturing firms in Nigeria during 2013 and 2022. For this, the paper tests two hypotheses: The first is that it assumes no significant relationship between working capital management and return on assets. The second assumes that working capital management does not significantly impact on return on equity of the companies in Nigeria. To evaluate this, we the study examines the relationship between working capital management variables, including stock turnover, debtor collection period, creditor collection period, and current ratio and performance indicators (return on assets and return on equity). The findings suggest that efficient management of these components enhances performance since stock turnover, debtor collection period, and creditor collection period are positively associated with financial performance. Because this has implication for future performance, the paper offers, amongst others that to enhance the profitability firms in Nigeria, there is the need to adopt more financial technologies can streamline working capital management processes, such as automating inventory and receivables tracking. Also, should be strategic extension of creditor collection periods without compromising supplier relationships to improve cash flow management. For instance, stricter credit control measures can be implemented to reduce the debtor collection period and can improve cash availability and profitability.